2019
DOI: 10.1371/journal.pgen.1008076
|View full text |Cite|
|
Sign up to set email alerts
|

Heterogeneous pathway activation and drug response modelled in colorectal-tumor-derived 3D cultures

Abstract: Organoid cultures derived from colorectal cancer (CRC) samples are increasingly used as preclinical models for studying tumor biology and the effects of targeted therapies under conditions capturing in vitro the genetic make-up of heterogeneous and even individual neoplasms. While 3D cultures are initiated from surgical specimens comprising multiple cell populations, the impact of tumor heterogeneity on drug effects in organoid cultures has not been addressed systematically. Here we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 75 publications
5
79
0
Order By: Relevance
“…In particular the NRAS G12C mutant showed higher sensitivity to most drugs than the other NRAS mutants, either due to the type of point mutation or other tumor intrinsic properties. Similar type of deviation in drug response was observed between KRAS mutants, confirming previous reports on CRC organoid biobanks with various RAS mutants 26,[44][45][46] . Overall, BRAF mutant CRC PDOs showed a very resistant phenotype to MAPK pathway inhibition.…”
Section: Crc Pdos With Different Mapk Pathway Mutations Display Varyisupporting
confidence: 90%
See 1 more Smart Citation
“…In particular the NRAS G12C mutant showed higher sensitivity to most drugs than the other NRAS mutants, either due to the type of point mutation or other tumor intrinsic properties. Similar type of deviation in drug response was observed between KRAS mutants, confirming previous reports on CRC organoid biobanks with various RAS mutants 26,[44][45][46] . Overall, BRAF mutant CRC PDOs showed a very resistant phenotype to MAPK pathway inhibition.…”
Section: Crc Pdos With Different Mapk Pathway Mutations Display Varyisupporting
confidence: 90%
“…While overall phenotypes per mutation showed resemblance, we did observe interclonal heterogeneity, in particular for NRAS. Presumably epigenetic and/or transcriptional differences between the cells-of-origin of the mutant clones can still affect phenotype 26,45 . For example, the most resistant NRAS G12D clone (#1) correlates with highest expression level and GTP-loading of the mutant protein ( Fig.…”
Section: Braf V600e and Kras G12d Knock-in Crc Pdos Show Resistance Tmentioning
confidence: 99%
“…This transition requires an accurate classification of drug-sensitive and -resistant PDOs. Similar to previous studies (28,29), OC PDOs were considered sensitive if the drug concentration that reduced viability of >50% of cells was lower than the concentration achievable in patient plasma (Css/Cmax). However, the Css/Cmax will vary between patients and is not necessarily the concentration that is achieved in the tumor (52,53).…”
Section: Discussionmentioning
confidence: 91%
“…Importantly, several studies have demonstrated that PDOs are amenable to drug screening within a clinically relevant timeframe (20,(23)(24)(25), and it was recently shown that PDOs can predict clinical responses (25)(26)(27), including to standard combination chemotherapies in a patient with mCRC (28). The pharmacological landscape of PDOs from CRCs has been investigated in a few studies (22,25,28), and there is evidence of intra-tumor heterogeneity in responses to selected drugs (29,30). However, the level of intra-patient inter-metastatic pharmacological heterogeneity is largely unknown.…”
Section: Introductionmentioning
confidence: 99%